2016
DOI: 10.3748/wjg.v22.i38.8596
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumor and solid-pseudopapillary neoplasm: Key immunohistochemical profiles for differential diagnosis

Abstract: AIMTo reveal better diagnostic markers for differentiating neuroendocrine tumor (NET) from solid-pseudopapillary neoplasm (SPN), focusing primarily on immunohistochemical analysis.METHODSWe reviewed 30 pancreatic surgical specimens of NET (24 cases) and SPN (6 cases). We carried out comprehensive immunohistochemical profiling using 9 markers: Synaptophysin, chromogranin A, pan-cytokeratin, E-cadherin, progesterone receptor, vimentin, α-1-antitrypsin, CD10, and β-catenin.RESULTSE-cadherin staining in NETs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…Two additional immunohistochemical markers commonly used to differentiate SPNs from NETs are synaptophysin and chromogranin; however, studies have shown that although these stains are highly sensitive for NETs, they lack specificity. Synaptophysin, in particular, though reported to be positive in up to 100% of NETs, has also been seen in the majority of SPNs . Chromogranin, though showing increased specificity for NETs in comparison with synaptophysin in some studies, has also been reported to show at least focal expression in up to 100% of SPNs and in more than 30% of acinar cell carcinomas in others …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Two additional immunohistochemical markers commonly used to differentiate SPNs from NETs are synaptophysin and chromogranin; however, studies have shown that although these stains are highly sensitive for NETs, they lack specificity. Synaptophysin, in particular, though reported to be positive in up to 100% of NETs, has also been seen in the majority of SPNs . Chromogranin, though showing increased specificity for NETs in comparison with synaptophysin in some studies, has also been reported to show at least focal expression in up to 100% of SPNs and in more than 30% of acinar cell carcinomas in others …”
Section: Discussionmentioning
confidence: 95%
“…4,22 Chromogranin, though showing increased specificity for NETs in comparison with synaptophysin in some studies, 22,23 has also been reported to show at least focal expression in up to 100% of SPNs and in more than 30% of acinar cell carcinomas in others. 4,24 We recently identified 2 additional immunohistochemical stains, SOX-11 and TFE3, that appear to be both sensitive and specific for SPNs on surgical resection. 6 In this study, we explore these 2 stains in the context of cytology and suggest that SOX-11 may be a useful adjunct in the differential diagnosis of SPN with EUS-FNA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…With regards to IHC assays, positive results with the beta-catenin stain and negative results with neuroendocrine markers, such as chromogranin A or synaptophysin, are important indicators that distinguish SPTs from pancreatic neuroendocrine tumors. 13 SPTs typically show indolent behavior and are associated with long survival rates (even in patients with disseminated disease) secondary to slow tumor doubling time (765 days). 14 Unfortunately, rapid tumor progression led to our patient's mortality 5 months after being diagnosed with this tumor.…”
Section: Discussionmentioning
confidence: 99%